APLICAÇÃO DA METODOLOGIA PEAKS OVER THRESHOLD AO SALTO EM COMPRIMENTO DO ATLETISMO - SILVA, Domingos; CAEIRO, Frederico; OLIVEIRA, Manuela (Brazilian Journal of Biometrics, 2018)
The Peaks Over Threshold (POT) method consists in the fit of a generalized Pareto distribution to a sequence of independent and identically distributed random excesses over a high threshold. In this study, we use the POT method to estimate the distributional parameters of excesses in the application of track and field long jump, between 1935 to 2016 in males, and 1964 to 2016 in females. After determining the appropriate threshold u, we present the estimates of some relevant parameters, like the exceedance probability, the extremal quantile, the right endpoint (only when gamma < 0), and the return levels and return period. In males, results point out to u=8.45m with gamma < 0 , and in females u=7.06m with gamma < 0 . It is expected that the world record will be beaten above 585 individual records in men, and above 427 individual records in women.